The traveling salesman problem and its variations - Gutin, Gregory, 1957-; Punnen, Abraham P. (Combinatorial optimization, 2002)
This volume provides information on theory and algorithms for the traveling salesman problem (TSP). The book covers all important areas of study on TSP, including polyhedral theory for symmetric and asymmetric TSP, and branch and bound, and branch and cut algorithms.